WorKshops as a Tool of Research and Learning - Macedo, Silvio Soares; Galender, Fany; Degreas, Helena; Cossia, Denis; Campos, Ana Cecília Arruda; Akamine, Rogério (Paisagem e Ambiente, 2009)
The present paper intends to present the workshops that have been held by the research The system of open spaces and the constitution of the contemporary public life in Brazil, which has been carried out in the Laboratório da Paisagem/Quadro do Paisagismo no Brasil – FAUUSP and supported by Fapesp. It is about the work process and the initial reflections on their contributions for the research, regarding six workshops that have been already done since 2007.